Broadly Engaged Team Science in Clinical and Translational Research - Lerner, Debra; Palm, Marisha E.; Concannon, Thomas W. (Cham : Springer International Publishing : Imprint: Springer, 2022)
Despite the large U.S. investment in health science, and the vast and growing body of peer-reviewed research findings it has produced, a compelling body of evidence suggests that research too often has been slow, inefficient, and fallen short of desired impacts on health. A key question is how research might be changed to be more innovative, less wasteful, and more responsive to unmet health needs. One emerging response within clinical and translational science is to advance an approach that attempts to close the gap between research scientists and key stakeholders; the individuals and groups responsible for or affected by health-related decisions. Broadly engaged team science promises to support this aim by transforming the gold standard, multi-disciplinary team science, to include key stakeholders in activities across the research spectrum. These new roles and responsibilities range from generating research questions to implementing research projects, to aiding in the translation of discoveries from the laboratory to the community. A transition to broadly engaged team science reflects the idea that inclusivity and a diversity of perspectives are necessary to achieving progress in addressing complex health issues while representing a new benchmark for ethical research practice. This is one of the first collections of papers describing how clinical and translational science researchers are defining and implementing new research practices, and the successes and challenges involved. This book represents a first and critical step towards organizing knowledge of broadly engaged team science and advancing the development of evidence-based practices. Written in an accessible style, this book is intended to highlight the breadth of broadly engaged team science within one community, motivate researchers and stakeholders to build inclusive teams, bring rigor to often informal stakeholder engagement research practices and encourage people to think more broadly about the development of scientific knowledge. It includes examples of multi-disciplinary, broadly engaged team science projects, the perspectives of academic leaders about the changes needed to encourage scientists to conduct broadly engaged team science, and a resource directory.
1. Introduction -- Part I Transforming Research with Broad Engagement -- 2. The Transformative Power of Broadly Engaged Team Science: A Moth-er's Quest to Understand PXE -- 3. Broadly Engaged Team Science in Neonatal Research -- 4. Patient Advocates in Cancer Care: A Rich Tradition and Evolving Role -- 5. National Kidney Foundation Patient Network -- 6. Broadly Engaged Team Science Comes to Life in a Design Lab -- 7. Tufts Center for the Study of Drug Development Employs Broadly Engaged Team Science to Explore the Challenges of Pharmaceutical Research and Development -- Part II. Integrating Communities and Stakeholders into Broadly Engaged Team Science -- 8. Social Movements and Stakeholder Engagement -- 9. A Basic Scientist's Journey: Engaging Public Stakeholders Through Civic Science -- 10. Lessons in Public Involvement from Across the Pond -- 11. Leveling the Playing Field for Community Stakeholders: Examining Practices to Improve Engagement and Address Power Dynamics -- 12. A Theory of Stakeholder-driven Community Diffusion -- 13. Monitoring and Evaluation of Stakeholder Engagement in Health Research -- Part III. Applying Broadly Engaged Team Science: Case Studies -- 14. Insiders and Outsiders: A Case Study of Fostering Research Partnerships between Academic Health Centers and Corrections Institutions -- 15. Responding to the Community: HOPE (Healthy Outcomes from Positive Experiences) -- 16. Students as Key Collaborators in Tackling Early Stage Research Ideas -- 17. Engaging Stakeholders to Decrease Study Start-up Delays -- 18. Health Literacy and Broadly Engaged Team Science: How One Study Team Used Plain Language Principles to Share Findings with Affected Communities -- 19. Utilizing Patient Navigators to Promote Equitable and Accountable Research -- 20. Asian American Research in the Post-Atlanta Era: Driving Community-engaged Research That Is More Meaningful, Responsive, and Actionable for Local Communities -- 21. Stakeholder Engagement in Predictive Model Development for Clinical Decision Support -- Part IV. Creating an Institutional Environment of Support for Broadly Engaged Team Science -- 22. Research Administration Practices for Proposal Development and Post-Award Management of Stakeholders and Community Participants -- 23. Starting Off Right: Supporting Community Involvement in the Evaluation of Research Proposals -- 24. Role of Broadly Engaged Team Science in the Inclusion of Minority Populations as Research Participants and in All Roles on Research Teams -- 25. Rewarding Team Science in Tenure and Promotion Practices: An Operational Imperative for the Academic Research Enterprise of the 21st Century -- Epilogue.
Keywords: Medicine-Research.; Biology-Research.; Clinical medicine-Research.; Public health; Political planning; Social medicine; Biomedical Research; Translational Research; Clinical Research; Public Health; Policy Formulation; Health, Medicine and Society